SERUM ESTRADIOL AND PROGESTERONE CONCENTRATIONS IN COWS WITH AND WITHOUT RETAINED PLACENTA - I., Al-Anbaghy, K.; K., Shareef, R.; H., Ali, A.; Fathalla, M. (The Iraqi Journal of Veterinary Medicine, 1989)
Serum samples from 8 Friesian cows with retained placenta and from 6 without retained placenta were analysed for estradiol 17B (E2) and progesterone concentrations by radiolimmunoassay. Results revealed that, mean E2 values in the affected COWS were higher than those of the unaffected, while progesterone levels did not differ significantly in both groups. Data have suggested that the increased estrogen level before parturition, toghether, with fall in the progesterone levels might be involved in the incidence of retained placenta.